Speaking, Reading, and Earnings among Low-Skilled Immigrants - Chiswick, Barry R. (Journal of Labor Economics, 1991)
This article is concerned with the determinants of English-language fluency among immigrants and the effects of fluency on earnings. Using special survey data on a sample of over eight hundred aliens, the analysis shows the importance of certain variables not previously available, speaking fluency at migration and English reading fluency. English speaking and reading fluency both increase with duration in the United States, and the increase with duration is greater for those with more schooling and who are not Hispanic. The article shows that reading fluency is more important than speaking fluency as a determinant of earnings. Copyright 1991 by University of Chicago Press.